HSP90α plays an important role in piRNA biogenesis and retrotransposon repression in mouse. Issue 19 (27th September 2014) - Ichiyanagi, Tomoko; Ichiyanagi, Kenji; Ogawa, Ayako; Kuramochi-Miyagawa, Satomi; Nakano, Toru; Chuma, Shinichiro; Sasaki, Hiroyuki; Udono, Heiichiro
Abstract: HSP90, found in all kingdoms of life, is a major chaperone protein regulating many client proteins. We demonstrated that HSP90α, one of two paralogs duplicated in vertebrates, plays an important role in the biogenesis of fetal PIWI-interacting RNAs (piRNA), which act against the transposon activities, in mouse male germ cells. The knockout mutation of Hsp90α resulted in a large reduction in the expression of primary and secondary piRNAs and mislocalization of MIWI2, a PIWI homolog. Whereas the mutation in Fkbp6 encoding a co-chaperone reduced piRNAs of 28–32 nucleotides in length, the Hsp90α mutation reduced piRNAs of 24–32 nucleotides, suggesting the presence of both FKBP6-dependent and -independent actions of HSP90α. Although DNA methylation and mRNA levels of L1 retrotransposon were largely unchanged in the Hsp90α mutant testes, the L1-encoded protein was increased, suggesting the presence of post-transcriptional regulation. This study revealed the specialized function of the HSP90α isofom in the piRNA biogenesis and repression of retrotransposons during the development of male germ cells in mammals.